The Relationship Between High-Risk Pregnant Women’s Knowledge and Their Readiness for Childbirth - Khilda Durrotun Nafisah; Roiful Fatah (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
High-risk pregnancy is a maternal health condition with a greater likelihood of complications that may adversely affect both mothers and newborns. Limited maternal knowledge regarding pregnancy risks often contributes to inadequate childbirth readiness, leading to delays in recognizing danger signs and seeking appropriate medical care. This study aims to analyze the relationship between maternal knowledge and childbirth readiness among high-risk pregnant women. A descriptive correlational design with a cross-sectional approach was employed. The study involved 100 high-risk pregnant women selected through purposive sampling in Kalibaru Wetan, Banyuwangi. Data were obtained through a validated and reliable questionnaire, and analyzed using the Chi-Square test. The results indicated that 67.0% of respondents had good knowledge, while 63.0% demonstrated high childbirth readiness. Cross-tabulation showed that mothers with good knowledge tended to have good readiness (89.6%), whereas poor knowledge was associated with low birth preparedness. Statistical analysis revealed a significant relationship between knowledge and childbirth readiness (p < 0.05), indicating that better maternal knowledge contributes to increased physical, psychological, and logistical readiness for childbirth. These findings highlight the importance of strengthening educational interventions targeting high-risk pregnant women, particularly through structured antenatal counseling, maternal health classes, and family involvement. Improved knowledge is essential not only for recognizing risk symptoms but also for enhancing confidence, decision-making, and preparedness to seek timely obstetric care. Health workers are recommended to implement participatory and continuous educational programs to optimize maternal readiness and ultimately reduce preventable maternal and neonatal complications.